If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = -3b + 5b Combine like terms: -3b + 5b = 2b 10 = 2b Solving 10 = 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. 10 + -2b = 2b + -2b Combine like terms: 2b + -2b = 0 10 + -2b = 0 Add '-10' to each side of the equation. 10 + -10 + -2b = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -2b = 0 + -10 -2b = 0 + -10 Combine like terms: 0 + -10 = -10 -2b = -10 Divide each side by '-2'. b = 5 Simplifying b = 5
| 4(4x-9)-7=4(x-2)+49 | | -3k+k=2 | | A^2-12ab+35b^2= | | 3(x+1)=2(x+4)-1 | | n+1+5n=-11 | | 5n^2-1=44 | | 20-4(2w+1)=8w-4(8+w) | | 336=-x(-2x-4) | | -2(-5a-4)+a= | | 65+x+(x-5)=180 | | x^2+7= | | x^2+3=16 | | 8b+4-2b=-14 | | 6(3-z)=-z | | 1+3(1+3x)= | | 7x+1=7X | | 6k+h=-14 | | 3x+2+x=(x+2)+3 | | 2(3z+2)-7=33 | | 5x+3=-6+3x+21 | | 7x-4=x+26 | | 3-.2y-1.4y=-9.2 | | -6(x-2)=24 | | 2(x-3)-17=13-3(x+20) | | 18y-11=76 | | 3(v+8)+6= | | (3x+8)=180 | | (9-z)(2z+7)=0 | | -6(x+2)=24 | | 44+30x=99+25x | | -5+5x=5(x+1) | | -6(x+12)=24 |